Faktor-Faktor Yang Mempengaruhi Minat Beli Sepeda Motor Bekas Pada UD. Irsan Motor - Suwanti Suwanti; Rohsita Amalyah Rasyid; Supriadi Supriadi; Ernawaty Mappigau (Jurnal Mirai Management, 2022)
This study aims to determine the factors that influence the interest in buying a secondhand motorcycle at UD. Irsan Motor in Tumbu Village, Topoyo District, Central Mamuju Regency. This research is a quantitative study with a simple random sampling method for three months until the number of samples is 50 used secondhand motorcycle buyers The results of this study indicate that product quality, price and promotion have a positive effect on buying interest. Promotion is the most dominant variable on interest in buying used secondhand motorcycles. Keywords: quality, price, promotion, interest